2021
DOI: 10.1080/09687637.2020.1858758
|View full text |Cite
|
Sign up to set email alerts
|

Overdoselifesavers.org: a mixed-method evaluation of a public information website on experiences of overdose and using take-home naloxone to save lives

Abstract: Aims: Overdoselifesavers.org was created as part of a larger Australian research project investigating impediments to take-home naloxone uptake. The aim of the project was to create a resource to enhance public and professional understandings of take-home naloxone and to counter stigmatising misconceptions about overdose. This article presents the findings of a mixed-method evaluation of Overdoselifesavers.org that assesses its success in achieving these goals. Methods: Following an established approach, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 57 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…A cross-sectional web-based survey and a mixed-methods study have demonstrated the unique position of bystanders in reversing opioid poisonings and saving lives, provided they are equipped with naloxone and the knowledge to administer it effectively (56,57). However, the bulk of these studies are based in the USA, with only one study conducted in Australia (33). Opioid poisoning is a global concern, demonstrating a pressing need to implement and evaluate virtual OPEND programs worldwide to increase access to this intervention (2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A cross-sectional web-based survey and a mixed-methods study have demonstrated the unique position of bystanders in reversing opioid poisonings and saving lives, provided they are equipped with naloxone and the knowledge to administer it effectively (56,57). However, the bulk of these studies are based in the USA, with only one study conducted in Australia (33). Opioid poisoning is a global concern, demonstrating a pressing need to implement and evaluate virtual OPEND programs worldwide to increase access to this intervention (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, the bulk of these studies are based in the USA, with only one study conducted in Australia(33). Opioid poisoning is a global concern, demonstrating a pressing need to implement and evaluate virtual OPEND programs worldwide to increase access to this intervention(2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations